PENGARUH ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN FOLLOWERS INSTAGRAM @KULINERPKU - Rahmadi, Yohanda; Lubis, Evawani Elysa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Electronic Word of Mouth on social media is a very important place for consumers to give their opinions and is considered effective than word of mouth because of the level of accessibility and wider range. In communication theory using computer intermediaries or commonly called Computer Mediated Communication theory examines how human behavior is maintained and changed by exchanging information through machines. This study aims to determine how much influence the Electronic Word of Mouth has on purchasing decisions on Instagram followers @kulinerpku.This research uses explanatory quantitative research methods. Data was collected by distributing questionnaires to 166 respondents Instagram @kulinerpku followers who had made a purchase decision. Data analysis using simple linear regression in the SPSS 23 for windows program.The results of the study with SPSS test, obtained the equation Y = 12,169 + 1,278 X, this shows that the results of the constant value (a) of 12,169 and the regression coefficient of X (electronic word of mouth) of 1,278. The partial test of electronic word of mouth has a t value of 12.451 with a significant level of 0.000. The significant value of electronic word of mouth is smaller than the significant level that is set at 0.05. From this it can be concluded that Ha is acceptable. The coefficient of determination test results obtained R Square value of 0.486. This shows that the percentage of the contribution of the influence of the independent variable (electronic word of mouth) to the dependent variable (purchasing decision) of 48.6% is classified as moderate, while 51.4% is influenced by other variables not examined in this research.Â Keyword : Electronic Word of Mouth, Purchase Decision